Dielectric and piezoelectric properties of BiFeO3 from molecular dynamics simulations - Graf, Mónica Elisabet (2015)
A first-principles based atomistic scheme is used to investigate the dielectric and piezoelectric properties of BiFeO3. The atomistic model fitted from first-principles calculations reproduces very well the structural and polar properties of the material at finite temperature, predicting a direct transition from a lowerature R3c ferroelectric phase to a Pbnm orthorhombic phase in agreement with experiments. We use this theoretical approach to calculate intrinsic single crystal properties, which are difficult to obtain from experiments due to decomposition and leakage problems. The whole set of dielectric and piezoelectric coefficients for BiFeO3 is computed as a function of temperature, together with the orientation dependence of the longitudinal coefficient d33∗.